THE ROLE AND IMPORTANCE OF THE PROTECTED AREAS’ (EMERALD NETWORK) DEVELOPMENT FOR AMPHIBIANS AND REPTILES ON THE EXAMPLE OF UKRAINE IN THE CONTEXT OF VARIOUS FACTORS’ INFLUENCE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Creation and expansion of the Emerald Network (EN) objects is one of the most promising directions of the nature conservation development in Ukraine according to European standards. The aim of EN objects designing is to assess the state of conservation of habitats and flora/fauna species’ populations on a pan-European level. It is assumed that the EN should cover at least 60% of the populations of species and the area of habitats mentioned in Resolutions (4 and 6) of the Berne Convention (1979). Later on, the EN will be integrated into Natura 2000 system. The other countries’ experience is of great importance in creating such territories. Since 2004 Latvia have joined this network and included 333 sites (12% of its territory). In Ukraine, such network is only being developed. Four Ukrainian biogeographical regions are inhabited by 6 amphibian and 5 reptile species for which according to Emerald Biogeographical Seminar ALP (Carpathians) - CON - PAN, 11-13 May 2016, Chisinau, Moldova, the EN in not sufficient, being indicated as IN MOD (moderately developed) in 90% of cases. A total of 63 suggestions of new EN (1628256,4 ha) objects aiming on herpetofauna conservation among others were designed during 2018-2019 and now are waiting to become candidate sites and later on – a part of Ukrainian EN. Most of these sites represent valuable territories of wild nature in the rivers’ floodplains. For Latvia and Ukraine conservation of marginal populations of the following species is important: crested newt Triturus cristatus (Laurenti, 1768), fire-bellied toad Bombina bombina (Linnaeus, 1761), pond turtle Emys orbicularis (Linnaeus, 1758). In the work the importance and the ways in which the EN can act for the above mentioned species’ conservation are highlighted, taking into account experience of European Union, future trends in the influence of anthropogenic factors, invasive species and climate change.